Strategi Pemasaran Sukuk Ritel seri SR019 Sebagai Instrument Keuangan Syariah - Arini, Erni Zulfa; Adiputra, Prasetia (Sharia Business Management Study Program, Faculty of Economics and Islamic Business at IAIN Kediri, 2023)
This study aims to determine the Government's strategy in an effort to issue and market the fifth series of Retail Government Securities (SBN) in 2023, namely the Retail Government Sukuk (SR) series SR019 in August. SR019 is the second Retail Sukuk offered by the government this year, after SR018 which was issued on March 3, 2023. Retail SBNs that have been issued by the government this year are, first, Retail Savings Bond (SBR) series SBR012, second, Retail State Sukuk (SR) series SR018, third, Savings Sukuk (ST) series ST010, and fourth, Retail State Bonds (ORI) series ORI023. This research uses qualitative methods with descriptive research types, data obtained from various sources arranged in narrative form. Based on the research results, it can be stated that the marketing strategy that has been implemented so far consists of two aspects of the marketing process and the marketing mix. The marketing process includes: (a) segmenting, namely retail and corporate; (b) the targeting carried out is in the form of a concerted targeting strategy; (c) positioning for conducting online savings Sukuk transactions. The marketing mix includes: (a) product in the form of SR019 Sukuk: (b) the price offered is very affordable for anyone, minimum IDR 1,000,000.00 and maximum IDR 10,000,000,000.00; (c) a place that is affordable, safe and comfortable; (d) promotion carried out through face to face seminars and online media; (e) people who have knowledge and experience; (f) physical evidence is equipped with complete facilities; (g) easy process.